The Association Between Vitamin E Deficiency and Critically Ill Children With Sepsis and Septic Shock - Dang, Hongxing; Li, Jing; Liu, Chengjun; Xu, Feng (Frontiers in Nutrition, 2021)
Background: Literature is scarce on the assessment of vitamin E status in septic children. We aim to investigate the prevalence of vitamin E deficiency in critically ill children with sepsis and septic shock and its association with clinical features and outcomes. Methods: We compared serum vitamin E status between the confirmed or suspected infection and no infection groups, the sepsis shock and no sepsis shock groups upon pediatric intensive care unit admission. Clinical characteristics were compared in subgroup patients with and without vitamin E deficiency. The association between vitamin E deficiency and septic shock were evaluated using univariate and multivariable methods. Results: 182 critically ill children with confirmed or suspected infection and 114 without infection were enrolled. The incidence of vitamin E deficiency was 30.2% in the infection group and 61.9% in the septic shock subgroup (P < 0.001). 30-days mortality in critically ill children with vitamin E deficiency was significantly higher than that without vitamin E deficiency (27.3%, vs. 14.2%, P < 0.05). Vitamin E levels were inversely associated with higher pediatric risk of mortality (r = − 0.238, P = 0.001) and cardiovascular sequential organ failure assessment (r= -0.249, p<0.001) scores in critically ill children with infection. In multivariable logistic regression, vitamin E deficiency showed an independent effect on septic shock (adjusted OR：6.749, 95%CI: 2.449-18.60, P<0.001). Conclusion: Vitamin E deficiency is highly prevalent in critically ill children with sepsis and contributed to the septic shock.